Pengembangan E-LKPD Berbasis Contextual Teaching and Learning Pada Materi Harga Pokok Proses Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa SMK - Ervina Novita Sari; Agung Listiadi (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2023)
This study aim to produce digital-based teaching materials in the form of E-LKPD using Contexual Teaching and Learning (CTL) by using the Application Flip Pdf Professional and integrated with activities that can train critical thinking skills of vocational students. This study uses the development model of Thiagarajan and Semmel (1974) which consists of 4 stages (define, design, develop, disseminate) due to time constraints the research was only carried out up to stage develop. The results of this study obtained are that the development of the E-LKPD that has been carried out can be categorized as very feasible with an average value of the validity test from material expert, language expert, graphic experts of 88.25%. The development of the E-LKPD received a very good response from students with a practicality analysis score of 97.19%. The E-LKPD that has been developed is effective in intensify students' critical thinking skills as evidenced by testing N-Gain score who obtained an average score of 61.83% which can be categorized as moderate based on the results of the critical thinking skills test. Thus, it can be concluded that the developed E-LKPD is categorized as valid and very feasible and can effectively improve the critical thinking skills of SMK students.